(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
XYZ Small Medium Enterprise (SME) is an SME that produces hijab. Research activities on XYZ aims to determine the operational cost of XYZ, caused by the far distance between the production site with retails. The analytical method which we use is by using the Center of Gravity. From the results of using the Center of Gravity method, the location of the new warehouse can be determined with the coordinates X = -7.51, Y = 110.45, which is located in Dusun II, Lencoh, Selo, Boyolali Regency, Central Java, XYZ can save distribution operational cost from IDR 22,711,150 to IDR 12,712,400. Therefore, XYZ can save distribution operational costs of IDR 9,998,750 or with a percentage of 55.97%. With the new distribution center location, it will shorten the distance from 1446 km to 264.6 km and reduce the transportation cost from the production site in Cicalengka, Bandung to the distribution center located in Dusun II, Lencoh, Selo, Boyolali Regency, Central Java.